2020
DOI: 10.3389/fmats.2020.00240
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Twinning on the Strain–Hardenability in TRIP/TWIP Titanium Alloys: Role of Solute–Solution Strengthening

Abstract: Transformation Induced Plasticity and Twinning Induced Plasticity (TWIP) titanium alloys are well-known to display a good combination of strain-hardenability and ductility. However, a large range of strain-hardening rates, which cannot be predicted by the actual design method based on electronic parameters, is obtained. In order to explain this wide range of properties, two different alloys displaying a large difference of strain-hardening rates, but similar chemical stability, have been studied and compared: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Overall, the evolution of the deformed microstructure in the case of the TCAF alloy shows the progressive development of a very dense network of {332}<113> twins as the primary deformation mechanism (Figure 2, Figure 3 and Figure 5). This may explain, as already observed in previous reports [25,[34][35][36], the high strain-hardening rate observed in this alloy.…”
Section: Figure 5: A) Ebsd Ipf Image Along the Rolling Direction Of A...supporting
confidence: 88%
See 1 more Smart Citation
“…Overall, the evolution of the deformed microstructure in the case of the TCAF alloy shows the progressive development of a very dense network of {332}<113> twins as the primary deformation mechanism (Figure 2, Figure 3 and Figure 5). This may explain, as already observed in previous reports [25,[34][35][36], the high strain-hardening rate observed in this alloy.…”
Section: Figure 5: A) Ebsd Ipf Image Along the Rolling Direction Of A...supporting
confidence: 88%
“…As the deformation proceeds, twins multiply in the grains, yet the deformation remains heterogeneous. The twin multiplication during the deformation is believed to explain the high and stable strain-hardening rate of the alloy, as proposed by the dynamic Hall-Petch mechanism [32][33][34] and further investigated in another study [35].…”
Section: Heterogeneous Microstructure and Localized Deformation In Lo...mentioning
confidence: 92%
“…The chemical composition of the alloy, and most particularly the oxygen content, is indeed of primary importance on the stress-induced β to α" phase transformation [53]. Grain sizes also influence the appearance of phase transformation and mechanical twinning in the deformation sequence of β-metastable alloys [54,55]. Finally, precipitation of α and/or ω phases also significantly influences the mechanical behavior of Ti-2448 [43,56].…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of α″ martensite on load removal was studied in Ti–27Nb, [ 57 ] Ti–24Nb–4Zr–8Sn, [ 59 ] Ti–10V–4Cr–1Al, [ 72 ] Ti5Al–5Mo–5V–3Cr, [ 63 ] Ti–12Mo–3Zr, [ 37 ] Ti–10V–2Fe–3Al, [ 34 ] and Ti–Mo [ 41,80 ] alloys.…”
Section: Reversion Of α″ Martensitementioning
confidence: 99%
“…[ 37 ] Qian et al [ 33 ] also suggested that de‐twinning processes on unloading could take place by {130}< 3 ¯ 10> α″ twins → {110}< 1 ¯ 10 > α″ twins → α″ martensite. In contrast, when Ti alloys were strained to a higher level (for example, 15% in Ti–12Mo), no reversion of α″ martensite on unloading was reported in Ti‐1023 [ 34 ] and Ti‐12Mo [ 80 ] alloys. It could be speculated that in alloys with superelastic behavior and a less stable β phase, the reversion process occurs with ease even when the fully α″ martensite microstructure is formed, but the limit of strain accumulation is not reached.…”
Section: Reversion Of α″ Martensitementioning
confidence: 99%